Treatment of class III malocclusion with activation-deactivation rapid palatal expansion and reverse headgear in a growing patient (alternate-rapid maxillary expansion and contraction) - Hemant Garg; Jagjit Kaur; Shivika Arya; Shahindah Shah (Wolters Kluwer Medknow Publications, 2020)
Treatment of Class III malocclusion is a challenge for orthodontists. The best time to intercept this malocclusion is as early as in the deciduous dentition. Orthopedic management of Class III individuals with retruded maxilla is by protraction facemask along with rapid maxillary expansion (RME). It results in forward and downward maxillary growth and backward mandibular rotation. Alternate RME and contraction (Alt-RAMEC) produces faster and more efficient results than maxillary protraction alone. The present case report describes the clinical application of Alt-RAMEC protocol for the treatment of a Class III malocclusion.